High Performance Computing - Severance, Charles; Dowd, Kevin (Open textbook library., 2021)
The purpose of this book is to teach new programmers and scientists about the basics of High Performance Computing. Too many parallel and high performance computing books focus on the architecture, theory and computer science surrounding HPC. This book speaks to the practicing chemistry student, physicist, or biologist who need to write and run their programs as part of their research.